2022
DOI: 10.1097/01.jaa.0000803628.10259.a9
|View full text |Cite
|
Sign up to set email alerts
|

PA licensure questions, the Americans with Disabilities Act, and seeking medical care

Abstract: Objective: This study built on a recent publication to explore physician assistant (PA) licensure renewal applications, as well as PA likelihood to seek help for physical or mental health conditions. Methods: We were able to obtain licensure renewal applications from 47 states. A national survey was then conducted to explore the connection between licensure questions and help-seeking behavior. Results: Only 18 states were consistent with the Americans with Disabilities Act (ADA) in their approach to initial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…As has been discussed for other healthcare professionals, the stigma associated with mental health problems may deter some PAs from acknowledging or seeking help for mental health issues. 9,41 Initiatives to promote help-seeking and enhance collegial or system supports may prevent some problems from escalating to suicide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been discussed for other healthcare professionals, the stigma associated with mental health problems may deter some PAs from acknowledging or seeking help for mental health issues. 9,41 Initiatives to promote help-seeking and enhance collegial or system supports may prevent some problems from escalating to suicide.…”
Section: Discussionmentioning
confidence: 99%
“…For example, physical or health problems (18.3%) or job problems (15.1%) were noted in a subset; the extent of their effect relative to other potential factors is not known. As has been discussed for other healthcare professionals, the stigma associated with mental health problems may deter some PAs from acknowledging or seeking help for mental health issues 9,41. Initiatives to promote help-seeking and enhance collegial or system supports may prevent some problems from escalating to suicide.…”
Section: Discussionmentioning
confidence: 99%
“…O nly 18 states have questions consistent with the Americans with Disabilities Act (ADA) when asking about mental and physical health on PA license applications or renewals. 1,2 This is an overlooked and potentially harmful defi cit.…”
mentioning
confidence: 99%
“…Recent studies have shown that only 18 states follow guidance from the Federation of State Medical Boards for questions about mental health on initial and/or renewal licensure applications, and that PAs in states that ask probing mental health questions are less likely to seek help for mental health issues or SUD 12,13. With so few states in compliance with guidance on best practices for licensure questions, there is cause for concern that many states will not adequately support PAs who may experience impairment.…”
mentioning
confidence: 99%